Eating disorders and health in elite women distance runners - Hulley, A. J.; Hill, A. J. (International Journal of Eating Disorders, 2001)
OBJECTIVES: To examine the presence of eating disorder syndromes in elite women distance runners in the United Kingdom and any associated differences in training, dieting, general health, and well-being. METHOD: Athletes were selected from the top of their respective ranking lists for all middle and long-distance races in 1996/1997. All running disciplines were included (track, road, cross-country, and fell/mountain running). Athletes were sent the Eating Disorders Examination Questionnaire and a questionnaire on demographics, athletic training, diet, and health. Of the 226 athletes identified, 181 (81%) completed and returned the questionnaires. RESULTS: Twenty-nine athletes (16%) had an eating disorder at the time of the study (7 had anorexia nervosa [AN], 2 had bulimia nervosa [BN], and 20 had eating disorders not otherwise specified [EDNOS]) and a further 6 had received previous treatment. Comparing the eating disorder group with the rest of the sample showed no difference in age, height, preferred race distance, or the number of hours/week spent training. However, they had a significantly lower body mass index (BMI), lower self-esteem, and poorer mental health. Current and past dieting were significantly more common in the eating disorder group. DISCUSSION: The levels of AN and EDNOS are higher than would be expected in similarly aged, nonathletic women. The demands for leanness rather than exercise intensity appear to be the main risk in these elite runners. The early detection and prevention of eating disorders in women athletes should have high priority.